The Tanzania Social Action Fund (TASAF) : Owning the Process of Measuring Impact and Achieving Results - Lenneiye, N.M. (World Bank, Washington, DC, 2012)
The Tanzania Social Action Fund (TASAF) is now in its second phase, covering the period 2005-2009. It is focused on giving more voice to citizens at both community and lowest local government levels - village councils. While retaining direct community financing as a key empowering mechanism, it is being implemented through Local Government Authorities. Target beneficiaries are: i) communities with inadequate access to social services; ii) households with able-bodied adults suffering from food insecurity; and iii) individuals living in poor households affected by acute shocks (like HIV/AIDS). These three beneficiary groups will access resources from a National Village Fund using procedures that build on the lessons learned regarding accountability, incomes poverty, and improving impact links.